Demographic processes and ethnic residential segregation - Itzhak Omer (Discrete Dynamics in Nature and Society)
This paper examines the involvement of demographic processes in the residential segregation of ethnic groups in an urban area. For this purpose, a two-part methodology has been employed. The first part comprises a conceptual framework which uses the concept of time–space resources as an analytical tool to clarify the structural constraints embedded in the changes in ethnic residential distribution. The second part comprises a simulation model of ethnic residential segregation. The model, which fits into the category of agent-based simulation models, serves as a tool for heuristic study. The methodology has been applied to examine the implications of fluctuations in ethnic group diffusion and the residential mobility rate on the majority–minority residential segregation, and on the internal ethnic segregation within the minority group.